β-Glucosidase Activity of Lactiplantibacillus plantarum: A Key Player in Food Fermentation and Human Health - Gianluca Paventi; Catello Di Martino; Francesca Coppola; Massimo Iorizzo (Foods)
β-glucosidases are a relevant class of enzymes in the food industry due to their role in hydrolyzing different types of glycosidic bonds. This activity allows for formation of volatile compounds and release of bioactive aglycone compounds. In addition to endogenous β-glucosidase activity present in raw material, the function of β-glucosidases in fermenting microorganisms has been progressively clarified and increasingly appreciated. In this regard, several lactic acid bacteria, including Lactiplantibacillus plantarum, showed high β-glucosidase activity, which can be considered as a valid biotechnological resource in different food sectors. Here, we reviewed the huge literature in which the β-glucosidases of L. plantarum were shown to play a role, highlighting how their action results in enhancing the nutritional, sensory, and functional properties of fermented foods. To this aim, after a brief introduction of the main functions of these enzymes in several kingdoms, we critically analyzed the involvement of L. plantarum β-glucosidases in plant-based food production, with a particular insight for soy, cassava, and olive-fermented products, as well as in the production of both alcoholic and non-alcoholic beverages. We trust that the reports summarized here can be helpful in planning future research and innovative strategies to obtain pleasing, functional, and healthy foods.